Offshore hydrocarbon resources in the Arctic: From cooperation to confrontation in an era of geopolitical and economic turbulence? - Maria Morgunova; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2016)
The Arctic region has been an area of low tension since the end of the Cold War. This observation is important because the run on hydrocarbons in the Arctic has not resulted in increased rivalries as expected. The outcomes have been international joint ventures in oil and gas project on the economic side and a strengthening of Arctic governance in the political realm. Since 2014, the situation has changed rapidly. Economic interests in hydrocarbon development are increasingly diverging between the five Arctic coastal states. The geopolitical situation between Russia and the West after the annexation of Crimea and military conflict in Ukraine affect the Arctic. There is the danger of falling back to old times when the Arctic was a highly strategic and militarised zone. The sanctions on Russian offshore oil development in the Arctic add to that. Potential long-lead effects of the sanctions, coinciding with relatively low oil prices, can seriously harm the long-term development of oil and gas fields in the Arctic. Joint energy projects had been a stabilising factor in the past. The paper discusses the increasing levels of instability in both economics and politics in the Arctic and the mutually reinforcing effects on international politics. We come to the conclusion that a 'loss of a cooperative spirit' can be observed. We argue that these dynamics challenge stable and predictable relations, which work against a sustainable Arctic development that takes the global commons, the environment and the climate into consideration. From a German and EU perspective, there are far-reaching future implications for the security of energy supply, as two of its major suppliers, Norway and Russia, have their resource bases in the Arctic. (SWP Research Paper)
Keywords: 320; Arktis; Arctic